Analisis Dan Perancangan Sistem Informasi Promosi Berbasis Web Pada IKM Kota Jambi - Desri, Desri; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2021)
The constraints faced by the Ministry of Industry and Trade is an additional cost to promote the products of IKM, but the income or income gained is not balanced due to the absence of a system that can promote well. Development of technology when it can accelerate the data processing related to the provision of promotion and information. Promotion and provision of information that is later presented in the form of websites, which will be developed to facilitate the management of promotional information existing in the Department of Industry and Trade of Jambi city The method used is the approach Object-oriented using the Unified Modeling Language (UML) modeling tool. This research resulted in a prototype that can be implemented into a system that can help market and promote the products of IKM in the industrial and trade office of Jambi City.